Connectionism and second language acquisition - Shirai, Yasuhiro, 1957- (New York, NY : Routledge, 2018)
'The latest title in the Cognitive Science and Second Language Acquisition series presents a comprehensive review of connectionist research in second language acquisition (SLA). Second language researchers and the cognitive science community will find accessible discussions of the relevance of connectionist research to SLA. This important volume is key reading for any student or researcher interested in how second language acquisition can be better understood from a connectionist perspective'--
Overview: connectionism and language acquisition research -- Connectionism and SLA research -- Rules vs. connections -- The critical period hypothesis -- Connectionist accounts and applications.
Includes bibliographical references and index.
Keywords: Second language acquisition; English language -- Study and teaching -- Foreign speakers; Connectionism